2020
DOI: 10.1186/s13293-020-00314-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in excessive alcohol use among older women across the menopausal transition: a longitudinal analysis of the Study of Women’s Health Across the Nation

Abstract: Background: Recent data suggest that excessive alcohol use is increasing among women and older adults. Such trends are concerning, as women are more vulnerable to alcohol-related health consequences, and such health problems may be exacerbated with age. Furthermore, there are sex-specific factors that may influence alcohol consumption among women, including the hormonal changes associated with the menopausal transition and negative affect. The present study sought to investigate transitions in excessive drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…Fifty-nine studies were extracted after abstract evaluation and 21 studies were finally included in the analysis, for a total of 30 trials (Figure 1). Among studies excluded, 12 studies enrolled only females, [53][54][55][56][57][58][59][60][61][62][63][64] 10 did not provide a control group, [65][66][67][68][69][70][71][72][73][74] 7 studies did not report hormonal data within the manuscript, [75][76][77][78][79][80][81] 5 did not measure T serum concentrations, [82][83][84][85][86] and 4 were duplicates of previous publications [87][88][89][90] (Figure 1). Table 1 summarizes data of included studies, of which 4 evaluated acute alcohol intake and 17 considered chronic alcohol intake.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-nine studies were extracted after abstract evaluation and 21 studies were finally included in the analysis, for a total of 30 trials (Figure 1). Among studies excluded, 12 studies enrolled only females, [53][54][55][56][57][58][59][60][61][62][63][64] 10 did not provide a control group, [65][66][67][68][69][70][71][72][73][74] 7 studies did not report hormonal data within the manuscript, [75][76][77][78][79][80][81] 5 did not measure T serum concentrations, [82][83][84][85][86] and 4 were duplicates of previous publications [87][88][89][90] (Figure 1). Table 1 summarizes data of included studies, of which 4 evaluated acute alcohol intake and 17 considered chronic alcohol intake.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that as women reach menopause, various environmental or psychosocial factors such as retirement and loss of loved ones, along with changes in body composition, may affect or exacerbate their drinking habits (Milic et al ., 2018 ). Based on the data from the SWAN study, although excessive alcohol consumption may not increase during MT, it is a period of instability that may be associated with changes in alcohol-related behaviours (Peltier et al ., 2020 ), which may also be driven by affective factors such as negative mood, retained stress and depressive symptoms related to menopause which may trigger suicidal ideation. Nevertheless, due to the cross-sectional nature of our study, it is difficult to draw conclusions regarding the role of alcohol use in the relationship between MT and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Além do mais, a transição da menopausa na maioria das mulheres é conhecida também pela instabilidade emocional4, isso devido à baixa hormonal e outros fatores que poderão levar ao consumo excessivo do álcool como uma escapatória para as emoções relacionadas a essa transição. Pesquisa atual insinua que o padrão de consumo alcoólico está aumentando na senilidade, o que poderá potencializar as doenças acometidas pela idade e também em mulheres, que são mais vulneráveis aos efeitos relacionados ao consumo exacerbado (Peltier et al, 2020).…”
Section: Discussionunclassified